Introducing the Tele-OCS: Preliminary evidence of validity for a remotely administered version of The Oxford Cognitive Screen [version 2; peer review: 1 approved, 2 approved with reservations] - Andrea Kusec; Nele Demeyere; Chloe Carrick; Sam S. Webb (Health Open Research, 2024)
Background Remote cognitive assessments are increasingly used with the rising popularity of teleneuropsychology. Here, we evaluated the performance of the remotely administered Oxford Cognitive Screen (Tele-OCS) compared to in-person administration in adult stroke survivors. Methods 40 stroke survivors (M age = 69.30, SD = 10.44; sex = 30% female) completed in-person and remote versions of the OCS on average 30 days apart, with different trained examiners. The order of administration was counterbalanced. Cohen’s d estimates were used to compare performance between modalities. Results We found that the proportion of OCS subtasks impaired did not differ across modalities (d <.001). With regards to raw subtask scores, only the picture naming subtask and executive score from the trail making subtask were found to be statistically different across modalities, though raw differences were minimal (<1 point difference on average). These statistical differences did not affect impairment classifications. Conclusions The Tele-OCS classified cognitive impairments in a comparable way to the in-person version. The validation of the Tele-OCS allows for remote assessment to increase accessibility and pragmatically aid in addressing the clinical need for stroke-specific cognitive screening in a wider population.